Microbiological assay for cefoxitin sodium in dosage form - Salgado, Hérida Regina Nunes [UNESP]; Gomes Tozo, Greici Cristiani (Aoac International, 2007)
A microbiological assay applying the cylinder-plate method is described for determination of the activity of cefoxitin sodium in injectables. Using a strain of Staphylococcus epidermidis ATCC 12226 as the test organism, cefoxitin sodium was measured in concentrations ranging from 50.0 to 200.0 mu g/mL. The validation showed that the method was linear (r = 0.9998), precise (RSD 0.81%), and accurate. It was concluded that the microbiological assay is satisfactory for quantitation of cefoxitin sodium in injectables.